P124 Catheter directed thrombolysis for acute pulmonary embolism: is it a service worth setting up?. (12th November 2019) - Bhamani, A; Devadas, K; Dawar, U; Hossain, S; Kabir, A; Pannu, K; Mukherjee, DK
Abstract : Background: Acute pulmonary embolism (PE) is a common disease with a variable clinical presentation. According to the British Lung Foundation, there were 2300 deaths from PE in 2012, equating to 2% of deaths from lung diseases in the United Kingdom. 1 While the management of low (small) and high (massive) risk PE is well established, the management of intermediate risk (sub-massive) disease is less certain. This is defined as acute PE without systemic hypotension but with either right ventricular dysfunction or myocardial necrosis. 2 Catheter directed thrombolysis (CDT) has been suggested as a potential treatment modality for such patients to reduce clot burden and right heart strain with lesser bleeding risk. Although CDT services are not well established in the UK, there is emerging evidence to suggest that ultrasound assisted CDT shows significant reduction in RV dilatation compared to anticoagulation alone without increased risk of bleeding. Methods: We conducted an audit to assess the prevalence of acute PE in patients presenting to our District General Hospital and assessed how many had evidence of right heart strain meeting proposed criteria for CDT. Indications for eligibility included PE Severity Index (PESI) class ≥III, troponin >14ng/l, CT ratio of RV: LV >1 and echocardiogram suggestive of pulmonary hypertension. Results: 360 patients underwent CTPA between April and June 2018. There were 60 positive scans. 22 patients met criteria for CDT. The average length of hospital admission for these patients was 12.76 days and 7 patients subsequently died. The most common indicator of right heart strain was PESI class ≥III (n=19) followed by RV: LV ratio >1 (n=14). 4 patients had saddle PE. Conclusion: 22 patients newly diagnosed with acute PE in our DGH would have met proposed criteria for catheter directed thrombolysis over a 3 month period. This equates to 88 patients annually. We believe that this data strengthens the argument for the development of regional hubs providing this service across the UK. References: https://statistics.blf.org.uk/pulmonary-embolism Konstantinides SV, Torbicki A, Agnelli G, et al . 2014 ESC guidelines on the diagnosis and management of acute pulmonary embolism. Eur Heart J 2014;35(43):3033–69.